Analyzing the Mechanism Between Local Government Debts and China’s Economic Development: Spatial Spillover Effects and Environmental Consequences - Cai, Xuesen; Song, Xiaowei (Frontiers in Environmental Science, 2022)
Under the new normal of economy, a series of active fiscal policies such as tax reduction and fee reduction and new infrastructure construction in China have reduced the source of local government revenue, while the expansion of fiscal expenditure and the widening gap between revenue and expenditure have further exacerbated the motivation of local governments to borrow. Using the spatial econometric model and based on the data of 30 provinces in China from 2006 to 2018, this paper deeply studies the impact of local government debt on economic growth and its spatial spillover effect, and discusses the regional location heterogeneity of this growth effect. The research shows that: (1) local government debt has significantly promoted regional economic growth; (2) The growth promoting effect of local government borrowing has significant spatial spillover; (3) Borrowing debt has the greatest effect on promoting economic growth in the central region, followed by the East, and the west is almost unaffected. Therefore, the Chinese government needs to continue to implement an active fiscal policy, improve the promotion and assessment mechanism of local officials, and adhere to the goal of balanced regional development